Effect of chewing hard material on boosting brain antioxidant levels and enhancing cognitive function - Kim, Seungho; Kim, Ji-Hye; Lee, Hansol; Jang, Sung Ho; Noeske, Ralph; Choi, Changho; Chang, Yongmin; Choi, Youn-Hee (Frontiers in Systems Neuroscience, 2024)
IntroductionChewing has been reported to enhance cognitive function through the increase in cerebral blood flow. However, the mechanisms linking cerebral blood flow increase to metabolic changes in the brain affecting cognition remain unclear. We hypothesized that glutathione (GSH) plays a pivotal role in these mechanisms. Therefore, this study aimed to investigate changes in brain GSH levels following chewing and their association with cognitive function in healthy young adults.MethodsA total of 52 university students were recruited, and the Korean version of the Repeatable Battery for the Assessment of Neuropsychological Status was used for the neurocognitive evaluations. Brain GSH levels following chewing gum or wood blocks were measured using MEscher-GArwood Point RESolved Spectroscopy (MEGA-PRESS) sequence, and their relevance to neurocognitive evaluation results was investigated.ResultsChewing significantly increased brain GSH concentration, particularly in the wood-chewing group compared to the gum-chewing group, as observed in the anterior cingulate cortex. Furthermore, the rise in GSH concentration in the wood-chewing group was positively correlated with memory function.ConclusionChewing moderately hard material elevates brain antioxidant levels such as GSH, potentially influencing cognitive function.